Memristive behavior of the SnO2/TiO2 interface deposited by sol–gel - Boratto, Miguel H. [UNESP]; Ramos, Roberto A. [UNESP]; Congiu, Mirko [UNESP]; Graeff, Carlos F.O. [UNESP]; Scalvi, Luis V.A. [UNESP] (Elsevier, 2017)
A novel and cheap Resistive Random Access Memory (RRAM) device is proposed within this work, based on the interface between antimony doped Tin Oxide (4%at Sb:SnO2) and Titanium Oxide (TiO2) thin films, entirely prepared through a low-temperature sol–gel process. The device was fabricated on glass slides using evaporated aluminum electrodes. Typical bipolar memristive behavior under cyclic voltage sweeping and square wave voltages, with well-defined high and low resistance states (HRS and LRS), and set and reset voltages are shown in our samples. The switching mechanism, explained by charges trapping/de-trapping by defects in the SnO2/TiO2 interface, is mainly driven by the external electric field. The calculated on/off ratio was about 8 × 102 in best conditions with good reproducibility over repeated measurement cycles under cyclic voltammetry and about 102 under applied square wave voltage.
Keywords: Memristor; Non-volatile memory; RRAM; SnO2/TiO2; Sol–gel; Thin film